Hormonal Changes Associated With Intra-Uterine Growth Restriction: Impact on the Developing Brain and Future Neurodevelopment - Baud, Olivier; Berkane, Nadia (Frontiers in Endocrinology, 2019)
The environment in which a fetus develops is not only important for its growth and maturation but also for its long-term postnatal health and neurodevelopment. Several hormones including glucocorticosteroids, estrogens and progesterone, insulin growth factor and thyroid hormones, carefully regulate the growth of the fetus and its metabolism during pregnancy by controlling the supply of nutrients crossing the placenta. In addition to fetal synthesis, hormones regulating fetal growth are also expressed and regulated in the placenta, and they play a key role in the vulnerability of the developing brain and its maturation. This review summarizes the current understanding and evidence regarding the involvement of hormonal dysregulation associated with intra-uterine growth restriction and its consequences on brain development.